The Vascular Swirls- Angiomatoid Fibrous Histiocytoma - Anubha, Bajaj (Journal of Clinical and Diagnostic Pathology, 2021)
Angiomatoid fibrous histiocytoma (AFH)  is an exceptional, soft tissue neoplasm of indeterminate lineage and intermediate malignancy associated with minimal localized tumour reoccurrence and infrequent distant metastasis. Preliminarily contemplated to be a variant or  derivative of malignant fibrous histiocytoma or undifferentiated pleomorphic sarcoma or an unusual fibrohistiocytic sarcoma,  angiomatoid fibrous histiocytoma predominantly incriminates young po pulation and superficial sites although several extra-somatic sites can be implicated.
Keywords: malignant fibrous histiocytoma; soft tissue neoplasia; Angiomatoid fibrous histiocytoma